2020
DOI: 10.1021/acs.chemmater.0c00419
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Formation of 2D/3D Heterostructures on the Edges of 2D Ruddlesden–Popper Hybrid Perovskite Crystals

Abstract: The observation of low-energy edge photoluminescence and its beneficial effect on the solar cell efficiency of Ruddlesden−Popper perovskites has unleashed an intensive research effort to reveal its origin. This effort, however, has been met with more challenges as the underlying material structure has still not been identified; new modelings and observations also do not seem to converge. Using twodimensional (2D) (BA) 2 (MA) 2 Pb 3 Br 10 as an example, we show that threedimensional (3D) MAPbBr 3 is formed due … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
80
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(84 citation statements)
references
References 50 publications
4
80
0
Order By: Relevance
“…Previous studies on 2D lead halide perovskites also have shown asymmetric PL line shape and attributed to extrinsic below gap trap states at surfaces/interfaces 33 , 43 . Layer edge states can also contribute the lower emission due the stochastic loss of organic ligands and formation of bulk CsPbBr3 perovskites 2 , 32 , 44 47 . However, lower energy emissions from below gap states or layer edge states exhibit longer lifetime compared with the band edge emission from 2D perovskites and persist at cryogenic temperature, if not be more pronounced 2 , 32 , 33 , 46 , 48 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on 2D lead halide perovskites also have shown asymmetric PL line shape and attributed to extrinsic below gap trap states at surfaces/interfaces 33 , 43 . Layer edge states can also contribute the lower emission due the stochastic loss of organic ligands and formation of bulk CsPbBr3 perovskites 2 , 32 , 44 47 . However, lower energy emissions from below gap states or layer edge states exhibit longer lifetime compared with the band edge emission from 2D perovskites and persist at cryogenic temperature, if not be more pronounced 2 , 32 , 33 , 46 , 48 .…”
Section: Discussionmentioning
confidence: 99%
“…1,3,[23][24][25] In addition, other studies indicate the presence of electronic states on the edges and dislocations of crystals correlate with broadband, subgap light emission from SAQW samples possessing the Ruddlesden-Popper structure. [26][27][28] Given the variation in experimental observations of the characteristics of subgap PL from hybrid SAQWs with so many different parameters of material formation, the general understanding of the mechanisms by which different types of electronic states participate in the trapping and recombination of excitons and charge carriers remains incomplete.…”
mentioning
confidence: 99%
“…13,19,21 Most importantly, we find this light emission feature is red-shifted by nearly 200 nm from the narrow photoluminescence emitted due free exciton recombination and possesses the broad bandwidth consistent with PL caused by so-called edge states in mixed cation, Ruddlesden-Popper hybrid perovskites reported by numerous authors. [26][27][28] Contrasting with previous studies, however, the 532 nm laser in our experiments excites the free exciton directly and allows us determine how the concentrations of molecular constituents in precursor solutions affect the photophysical properties of hybrid SAQWs. In particular, driving the exciton resonantly not only allows us to discount trapping of charge carriers photo-generated promptly with higher energy light, but also allows us to use power-dependent PL spectra and investigate the excited state processes driving subgap PL in our samples, as we discuss in more detail below.…”
mentioning
confidence: 99%
“…1,3,[23][24][25] In addition, other studies indicate the presence of electronic states on the edges and dislocations of crystals correlate with broadband, subgap light emission from SAQW samples possessing the Ruddlesden-Popper structure. [26][27][28] Given the variation in experimental observations of the characteristics of subgap PL from hybrid SAQWs with so many different parameters of material formation, the general understanding of the mechanisms by which different types of electronic states participate in the trapping and recombination of excitons and charge carriers remains incomplete.…”
mentioning
confidence: 99%